Case report: Ruxolitinib plus dexamethasone as first-line therapy in haemophagocytic lymphohistiocytosis - Zhao, Lin; Yang, Hui; Qu, Wei-ying; Lu, Ying-jia; Feng, Zhou (Frontiers in Oncology, 2023)
Haemophagocytic lymphohistiocytosis (HLH) is a cytokine-driven inflammatory syndrome caused by uncontrolled hypersecretion of inflammatory cytokines. Conventional first-line treatment for HLH included HLH-94 and HLH-2004 regimens. However, quite a few patients do not respond to treatment or cannot tolerate intensive chemotherapy. We reported two cases of HLH, one caused by natural killer (NK)/T-cell lymphoma and another associated with missense variants in the perforin 1 gene. They both received the ruxolitinib plus dexamethasone protocol and had a rapid response to treatment without obvious adverse effects. Our report indicates that treatment with ruxolitinib plus dexamethasone might be a potential option for HLH, and clinical trials warrant further investigation. In addition, the detection of HLH-related genes is necessary for the identification of late-onset familial HLH in certain settings.